Factors affecting the efficiency of the use of disc brake systems of wheeled vehicles (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The prevailing requirements for modern rolling stock necessitate an increase in its speed. To achieve the requisite efficiency and operational quality of a vehicle, paramount attention must be directed towards ensuring a high level of traffic safety. The braking system plays a crucial role in upholding road traffic safety. Consequently, the demands for the reliability of an automobile's braking system to safeguard traffic have become more stringent. This study provides an extensive overview of disc brake systems in automobile transport and delves into the principal factors influencing their operational efficiency. The review underscores that the geometric characteristics of disc brakes are contingent upon load capacity and operational conditions. These considerations must be meticulously accounted for during the initial design phase, alongside the selection of manufacturing materials. The operational experience of disc brakes reveals that the friction pair (comprising pads and disc) operates under challenging conditions, given the simultaneous occurrence of static, dynamic, and thermal loads during braking. In most instances, the design of disc brakes should preclude overheating between the disc and the pad, a phenomenon triggered by friction during braking. The physical, mechanical, and chemical properties of the materials employed significantly influence braking behavior and performance. The duration of brake disc usage is further impacted by the seamless operation of all adjacent components. The high efficiency of the braking system necessitates the incorporation of elements characterized by both high quality and reliability.
Keywords: automobile; brake mechanism; disc brakes; efficiency of use; friction pairs; wear; friction materials